Penggunaan Istilah dalam Komunikasi Psikiater dengan Keluarga Pasien RSUP Dr. Sardjito Yogyakarta - Anugrah Dany Setiawan (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2019)
The purpose of research is to determine the perceptions of psychiatrists and patients' families. This method of research is non-experimental research with a sectional cross design. How data collection comes under direct observation, interviews, and a dialog record to the patient's family in RSUP Dr. Sardjito, Yogyakarta. The subject of this research is the patient's family and psychiatrist. The data validity test was triangulated medical records, psychiatrists and patients' families. Sources of data this research are events and informants. Techniques employed in collecting data include (1) immediate observation, (2) interviews, (3) recording, and (4) analysis. Among the characteristics of the psychiatrist with the patient's family records: (1) diagnosis, (2) drug regulation (3) control issues, and (4) prognosis. The purpose of the register between the psychiatrist and the patient's family is to have psychiatric communication with the patient's family on target. The measuring material is a suitable questionnaire between the psychiatrist's explanation and the understanding of the patient's family after the patient is discharged from RSUP Dr. Sardjito. Research has concluded that there's no research register for communication between the psychiatrist and RSUP Dr. Sardjito's family of patient.